Investigation and characterization of functional nucleic acids in whole human serum for the detection of biomarkers towards diagnostic application - Cozma, Ioana (My University, 2023)
Steady advancements in diagnostics over the past century have propelled the world of medicine into the more advanced era of preventative medicine, an era with a resoundingly clear message: early detection can save lives. For patients who suffer from either pancreatic cancer or malignant hyperthermia susceptibility, early or preoperative diagnosis, respectively can save lives and minimize morbidity and mortality, in addition to offering cost-savings to hospitals and healthcare systems. Fortunately, significant progress have been made in the fields of metabolomics and biomarker identification. Given the benefits carried by serum biomarkers as targets of screening and diagnostic tool development, we applied functional nucleic acid technology and in vitro selection directly in whole human serum to search for disease-specific biomarkers and associated detection probes without a priori knowledge of the biomarkers pursued. This endeavour simultaneously serves as a proof-of-concept study to establish whether in vitro selection can be successfully performed in human serum. We specifically focused on the derivation of RNA-cleaving DNAzymes (RCD) through in vitro selection, or SELEX (systemic evolution of ligands through exponential exposure). DNAzymes constructed with a fluorogenic signalling molecule were incubated with human serum with the goal of identification of a functional nucleic acid probe capable of detecting the presence of a disease-specific biomarker. Two independent protocols have been designed and executed for the identification of DNAzyme sequences capable of detecting pancreatic cancer and malignant hyperthermia susceptibility, respectively. The first exploration was performed in serum obtained from cancer patients, with the goal of identifying DNAzymes capable of distinguishing pancreatic cancer from other cancer types. To do so, we employed in vitro selection, Next-Generation Sequencing, and bioinformatic analysis. We successfully demonstrated the feasibility of performing in vitro selection with DNAzymes in human serum, evidenced by distinct round-to-round enrichment of a DNA library towards the identification of DNAzymes capable of detecting pancreatic cancer. Additionally, we isolated two DNAzymes capable of distinguishing pancreatic cancer serum from healthy patient serum in fresh collected serum samples. Based on the positive results gathered in the pancreatic cancer in vitro selection project, we subsequently endeavoured to replicate the demonstrated feasibility of performing in vitro selection in human serum. By selecting malignant hyperthermia as the pathology investigated, we simultaneously sought to diversify the scope of DNAzyme detection by establishing whether successful DNAzyme selection can be achieved in a non-acute disease state. Thus, the second exploration was performed in serum obtained from patients who underwent evaluation for malignant hyperthermia susceptibility using the gold-standard caffeine-halothane contracture test. The goal of this project rested on the identification of DNAzymes capable of distinguishing malignant hyperthermia susceptibility in serum and approximating the performance of the gold standard test. We successfully isolated four DNAzyme candidates which demonstrated clinically relevant thresholds of sensitivity and specificity following thorough sensitivity and specificity analysis. In doing so, we once again demonstrated the ability to perform in vitro selection in human serum. Given the complexity of molecular interactions observed over the course of two in vitro selection protocols in human serum, it became clear that distinguishing meaningful target-mediated interactions from non-specific interactions would require advanced bioinformatic analysis. Consequently, using principles of computational biology, we performed a deep exploration of Next-Generation Sequencing results obtained from sequencing our recovered DNA libraries to extract additional data that would inform on the next required steps required to identify a DNAzyme specific for the pathology pursued. In doing so, we identified a two-step method to evaluate the progress of the in vitro selection protocol undertaken, and offered a systematic approach for choosing candidate sequences to undergo further testing based on promising performance in silico. Using this approach, we successfully identified a DNAzyme sequence capable of acting as a general cancer detection probe, with promising potential for diagnostic application. Ultimately, this thesis serves as a feasibility study of a novel approach to both in vitro selection and biomarker identification technique by combining the latest nanotechnology techniques with clinical data and real patient serum samples, and advanced computational biology tools. Despite the inability to identify a highly sensitive and specific DNAzyme capable of advancing towards biosensor construction, several important strides and lessons have been acknowledged, establishing the feasibility of performing in vitro selection in human serum, and outlining strategies for addressing and anticipating challenges with this technique. The hope is for this work to inspire and inform future efforts to apply functional nucleic acid technology to solve current gaps in both the diagnostic and therapeutic branches of medicine, and with the help of computational biology continue to bridge the gap between basic science and clinical medicine.
Investigation and characterization of DNAzymes in whole human serum for the detection of biologic targets towards biosensor application
Keywords: Functional nucleic acids; Diagnostics; Pancreatic Cancer; Malignant Hyperthermia; DNAzymes; Serum; Human serum